Heterostructured intermetallic CuSn catalysts: high performance towards the electrochemical reduction of CO2 to formate - Wang, Jigang; Zou, Jiasui; Hu, Xiao; Shunlian Ning; Wang, Xiujun; Kang, Xiongwu; Chen, Shaowei (Journal of materials chemistry. A, Materials for energy and sustainability, 2019)
Electroreduction of carbon dioxide (CO2RR) into fuels and chemicals is an appealing approach to tackle CO2 emission challenges. To this end, it is critical to develop highly efficient and selective electrocatalysts for the CO2RR. Herein, we report a simple strategy for the preparation of heterostructured intermetallic CuSn electrocatalysts (Cu3Sn/Cu6Sn5) supported on porous copper foam through an electrodeposition–calcination process. The obtained CuSn intermetallic catalysts demonstrate a faradaic efficiency of 82% and a current density of 18.9 mA cm−2 at −1.0 V vs. the reversible hydrogen electrode for formate production in 0.1 M NaHCO3 electrolyte for as long as 42 h. By using a gas diffusion electrode and 1 M KOH electrolyte, the current density of this catalyst for formic acid production can reach values as high as 148 mA cm−2. Density functional theory calculations show that the moderate Gibbs free energy of hydrogen adsorption on the heterostructured Cu3Sn/Cu6Sn5 catalysts not only suppresses hydrogen evolution, but also favors the production of formic acid. This study demonstrates a straightforward approach to the preparation of high-performance electrocatalysts towards the selective electroreduction of CO2 to formate.